How China opened its door : the political success of the PRC's foreign trade and investment reforms - Shirk, Susan L. (Brookings Institution, 1994)
China's transformation from a virtually closed economy to a major trading nation is an incredible success story. Since 1979 the country has changed its policies to promote increased foreign trade and investment, thereby attracting more direct investment to China than to any other developing country in recent years. What brought about this change? How, after thirty years of being walled off from the world economy, did China open its door? This book, part of the Brookings Integrating National Economies series, tells the story of how China ended its long-held policies of economic isolationism and rejoined the world economy in the decade and a half between 1979 and 1994. It shows how China's transformation into a world trading power was achieved remarkably without any major alteration in the country's communist political system. Susan L. Shirk describes the reform strategy and explains why such a turnaround was possible in China but not in the Soviet Union.
Keywords: China -- Commercial policy.; China -- Economic policy -- 1976-2000.; Chine -- Politique économique -- 1976-2000.; POLITICAL SCIENCE -- Public Policy -- Economic Policy.; BUSINESS & ECONOMICS -- Government & Business.; BUSINESS & ECONOMICS -- Development -- Economic Development.; BUSINESS & ECONOMICS -- Development -- Business Development.; BUSINESS & ECONOMICS -- Structural Adjustment.; BUSINESS & ECONOMICS -- Development -- General.; Politique commerciale.; Politique économique.; Chine.; Commercial policy; Economic policy; China; Außenhandelspolitik; Economische hervormingen.; Handelspolitiek.; BUSINESS & ECONOMICS / International / General; 1976-2000; Geschichte 1979-1994.